Risk Management in Customs Control - Drobot, Elena Valerievna; Klevleeva, Aziza Renatovna; Afonin, Petr Nikolaevich; Gamidullaev, Siradzheddin Nagmetullaevich (Economy of Regions, 2017)
Customs administrations operating in the modern global economy are faced with a complex range of challenges. The prime responsibilities remain the collection of revenues and the protection of the society, but these demanding tasks must be performed effectively and efficiently, whilst at the same time facilitating the flow of legitimate goods. Risk management is a logical and systematic method of identifying, analyzing and managing risks. Risk management can be associated with any activity, function or process within the organization and will enable the organization to take advantage of opportunities and minimize potential losses. Minimization of the human factor in customs control through the implementation of non-intrusive inspection equipment can be very useful. The particularities of risk-management system (RMS) implementation within customs control are discussed in the article. The authors single out the elements of the risk-management system, evaluate the effectiveness of risk-management in customs control. The main reasons for non-implementation of the risk-management system in customs control are described as well. The particular attention is paid to the benefits of customs risk management. The authors’ hypothesis is that risk management in customs control must find a balance between costs and benefits to address all risks equally. Criteria are needed to decide what constitutes an acceptable or unacceptable risk. Thus, system analysis and risk management system are the effective mechanisms for acceleration of customs clearance and improve the quality of customs control. As a conclusion, the authors give recommendations for the improvement of the effectiveness of risk management system in customs control.